PRODUCT INNOVATION STRATEGIES AND MARKET ORIENTATION TO IMPROVE MARKETING PERFORMANCE AT MEATBALL MSMES IN BEKASI CITY - Syahyono, Syahyono; Arifin, Nasjwa Putri Syachrah; Pearl, Sonia; Shalihin, Fikri Radiatus (Jurnal Manajemen dan Bisnis, 2025)
Fierce competition in the meatball industry encourages MSMEs to innovate in products and marketing strategies. Product innovations such as flavor variants, raw material quality, and unique presentation can increase consumer appeal. In addition, a market orientation that understands customer needs and preferences is a key factor in increasing satisfaction and market share. However, the relationship between product innovation, market orientation, and marketing performance still needs to be further researched to provide new insights for MSMEs in increasing their competitiveness. Research method: This study uses a qualitative approach with in-depth interviews with MSME meatball owners and actors in Bekasi City and observation of the marketing process applied. The results of the study show that, simultaneously and partially, the orientation of market orientation variables, product creativity, and product innovation innovation have a positive and significant effect on the marketing performance of Meatball MSMEs in Bekasi City. Therefore, the right product innovation strategy and market orientation that focuses on consumer needs and desires can be key factors in improving the competitiveness and marketing performance of MSMEs. that product innovation, such as the development of flavor variants, the quality of raw materials, and innovations in presentation, plays an important role in attracting consumers' attention. In addition, market orientation based on understanding consumer preferences and product adaptation to market trends has been proven to increase customer satisfaction and expand market share. This study shows that market orientation has a significant effect on the marketing performance of Meatball MSMEs in Bekasi, while product innovation has a smaller direct influence. However, innovation still plays a role in strengthening market orientation. Therefore, MSMEs are advised to focus more on understanding market needs while continuing to innovate in order to increase their competitiveness and business growth.